Exploring meditation - "Shumsky, Susan G." (New Delhi, 2003)
This spiritual self-help book brings the esoteric world of meditation and Eastern philosophy to people from all walks of life. This book does not assume any prior experience in inner exploration. It offers easy, step-by-step procedures to master the anc
Keywords: Meditation